Low-melting-point metal melt-bonded iron-air battery negative electrode, preparation method and application thereof
Patent Information
- Application Number
- CN202611229733.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-30
AI Technical Summary
[0007]上述现有铁电极技术存在以下共性技术问题:(1)均须使用聚合物粘接剂(聚乙烯、聚四氟乙烯等,约10~15wt%)维持电极机械完整性,而聚合物为电子绝缘体(电导率通常低于10-14S/m),在电极内部形成绝缘网络,显著增大电极欧姆内阻;(2)为弥补聚合物导致的导电性下降,须额外使用碳系导电剂(炭黑、科琴黑等,约3~5wt%),而碳材料在反复充放电及空气电极侧高电位工况下存在缓慢氧化损耗的长期稳定性隐患;(3)聚合物粘接剂与碳系导电剂均为电化学惰性组分,合计占据电极质量的15%~20%,显著压缩活性物质比例、降低电极有效能量密度;(4)金属组分(铋、锡、铟等)仅作为少量功能性添加剂使用,且多以氧化物/硫化物前驱体形式加入,需经历多个充电循环的原位还原活化过程方能发挥作用,存在明显的活化期效率损失;(5)现有技术的热压/压制温度均远低于上述金属的熔点,金属在电极中始终以分立颗粒或电沉积薄层形式存在,未被赋予结构性粘结功能;(6)电极须依附于集流体网/板成型,集流体作为非活性组件进一步增加电极质量与成本
(1)传统负极必须添加绝缘聚合物粘接剂与碳导电剂,惰性组分挤占活性材料比例。本发明依靠熔融低熔点金属形成连续金属网络,替代两类惰性辅料,铁基活性物质占比显著提高,电极能量密度提升。
Smart Images

Figure CN123017994A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochemical energy storage technology, and in particular to a low-melting-point metal molten bonded iron-air battery anode, its preparation method, and its application. Background Technology
[0002] With the rapid increase in the installed capacity of intermittent renewable energy sources such as wind and solar power, the demand for long-duration energy storage (LDES) in the power grid is becoming increasingly urgent. The typical discharge time of lithium-ion batteries is only a few hours, making it difficult to economically meet the energy transfer needs on a daily or even multi-day timescale. Iron-air batteries, using metallic iron as the negative electrode active material, oxygen from the air as the positive electrode active material, and concentrated potassium hydroxide aqueous solution as the electrolyte, have a theoretical electromotive force of approximately 1.28V and a theoretical specific capacity as high as 960mAh / g. Furthermore, iron resources are abundant, inherently safe, and there is no risk of thermal runaway, making them one of the most promising long-duration energy storage technologies. Currently, some companies are already conducting commercial deployments and grid-connected demonstrations of 100-hour-level iron-air battery systems.
[0003] However, alkaline iron-based secondary batteries, represented by iron-air batteries, have long faced three major technical bottlenecks hindering their commercialization. First, low charging efficiency: the hydrogen evolution reaction during charging (standard potential approximately -0.828 V vs SHE) thermodynamically precedes iron reduction (Fe(OH)2 / Fe, approximately -0.877 V vs SHE), resulting in a significant amount of charge being consumed in hydrogen production, leading to low coulombic charging efficiency. The charging efficiency of the iron electrode in commercial nickel-iron batteries is typically only 55%–70%. Second, poor high-rate discharge capacity: the discharge product ferrous hydroxide is an electronic insulator, forming a dense passivation film on the surface of active particles, blocking electron and ion transport and causing a sharp decline in high-rate discharge capacity. Third, cycle capacity degradation: the irreversible generation of low-electrochemically active phases (such as γ-Fe2O3 and dense Fe3O4) during cycling causes continuous capacity decay.
[0004] To address the aforementioned issues, various improvement solutions have been developed in the existing technology. US Patent US10,374,261B2 and its European counterpart EP2721688B1 (University of Southern California) disclose a high-efficiency iron electrode that uses carbonyl iron powder as the active material and adds metal sulfides or metal oxides selected from bismuth, lead, mercury, indium, gallium, and tin (such as Bi₂O₃ and Bi₂S₃) to suppress hydrogen evolution during charging. The bismuth additives are electrochemically reduced in situ to form a metallic bismuth deposit during charging. The pressed plate electrode of this patent is hot-pressed at approximately 140°C (far below the melting point of bismuth (271.4°C), tin (231.9°C), and indium (156.6°C) using a polymer binder such as polyethylene. According to the patent, it can achieve a maximum charging efficiency of approximately 96% and a specific capacity of approximately 0.3 Ah / g. Relevant academic literature (Manohar et al., J. Electrochem. Soc., 2012, 159(8):A1209; 2013, 160(11): A2078) reported the mechanism by which bismuth oxide and ferrous sulfide additives synergistically improve the charging efficiency to about 92% and obtain a discharge specific capacity of about 0.2 Ah / g at 3C rate; the role of sulfide additives in inhibiting passivation of alkaline iron electrodes has also been reported in a large number of literatures.
[0005] Chinese patent application CN112805851A discloses a negative electrode for electrochemical batteries, employing a composite metal electrode composed of spherical metal agglomerates (such as directly reduced iron agglomerates or iron ore agglomerates) and powdered metal raw materials. The electrode is formed by agglomerate bed stacking structure, but does not involve low-melting-point metal fusion bonding structures. Furthermore, existing research on binder-free electrodes (such as in-situ growth of metal nanosheets on nickel foam or carbon fibers as negative electrodes for sodium-ion batteries) largely relies on wet processes such as solution displacement and electrodeposition to grow active materials in situ on the substrate surface. These processes are complex, have low loading capacity, and are not suitable for materials with micron-sized metal powder as the main component and surface loading capacities as high as tens of mg / cm³. 2 Mass production of alkaline iron-air battery anodes.
[0006] The idea of using metals as binders has been sporadically reported in other battery systems. US Patent 5,124,120 discloses a method for preparing a zinc electrode for an alkaline zinc battery. This method involves mixing zinc-magnesium "binding alloy" powder with a melting point of approximately 363–415°C with a second zinc alloy powder with a higher melting point, then heating the mixture to a temperature between the two melting points to melt the binding alloy, thereby binding the zinc active particles together. However, in this scheme, the binding alloy itself is the zinc active material, participating in the dissolution-deposition reaction during charge and discharge, and its melting point is above 350°C. This scheme does not involve iron electrodes, nor does it address the structural design for hydrogen evolution suppression and solidification expansion locking. Other liquid metal batteries use molten bismuth, tin, etc., as high-temperature liquid electrodes (operating temperatures typically above 300°C), or room-temperature liquid gallium-based alloys as electrode components. In these schemes, the metals are in a liquid state during battery operation and participate in the electrode reaction as energy storage active materials.
[0007] The existing iron electrode technologies mentioned above have the following common technical problems: (1) They all require the use of polymer adhesives (polyethylene, polytetrafluoroethylene, etc., about 10-15 wt%) to maintain the mechanical integrity of the electrode, while polymers are electronic insulators (the conductivity is usually less than 10). -14 (2) To compensate for the decrease in conductivity caused by the polymer, carbon-based conductive agents (carbon black, Ketjen black, etc., about 3-5 wt%) must be used. However, carbon materials have a long-term stability risk of slow oxidation loss under repeated charging and discharging and high potential conditions on the air electrode side. (3) Both polymer binders and carbon-based conductive agents are electrochemically inert components, accounting for 15%-20% of the electrode mass, which significantly compresses the proportion of active materials and reduces the effective energy density of the electrode. (4) Metal group (5) Bismuth, tin, indium, etc. are used only as small amounts of functional additives and are mostly added in the form of oxide / sulfide precursors. They need to undergo an in-situ reduction and activation process of multiple charging cycles to play a role, resulting in a significant loss of activation efficiency; (6) The hot pressing / pressing temperature of the existing technology is much lower than the melting point of the above metals. The metals always exist in the electrode in the form of discrete particles or electrodeposited thin layers and are not given structural bonding function; (7) The electrode must be attached to the current collector mesh / plate for forming. The current collector, as an inactive component, further increases the electrode quality and cost.
[0008] Therefore, there is an urgent need in the field for an iron-air battery anode and its preparation technology that can simultaneously eliminate polymer binders and carbon-based conductive agents, simplify electrode formulation, increase the proportion of active materials, maintain high charging efficiency and good cycle stability, and flexibly select whether to use current collectors and solid-phase functional additives according to the application scenario. Summary of the Invention
[0009] This invention provides an iron-air battery anode that simultaneously achieves bonding and conductivity functions through a continuous metal network formed by melting and solidification of a low-melting-point metal, as well as a method for preparing the anode, an iron-air battery containing the anode, and its applications. This invention overcomes the technical limitations of existing iron-air battery anodes, which must rely on polymer binders and carbon-based conductive agents, where the metal components can only play a single function in the form of small amounts of additives and suffer from activation period loss, and where the electrode structure depends on current collectors.
[0010] This invention provides a low-melting-point metal-bonded iron-air battery anode. The anode includes an active layer comprising iron-based active particles and a low-melting-point metal-bonded conductive phase. The active layer contains no polymer binder or carbon-based conductive agent. The low-melting-point metal-bonded conductive phase is a continuous three-dimensional metal network formed by a melting-solidification process of a low-melting-point metal with a melting point of 130–350°C. This continuous three-dimensional metal network forms a bridging structure at the contact necks of adjacent iron-based active particles, bonding the iron-based active particles together and forming a continuous electron conduction pathway within the active layer. The content of the low-melting-point metal-bonded conductive phase, based on the total mass of the active layer, is 5–25 wt%.
[0011] The low-melting-point metal fusion-bonded iron-air battery negative electrode provided by the present invention is wherein the low-melting-point metal is bismuth, tin, or lead, or is an alloy containing at least one of bismuth, tin, and lead.
[0012] The low-melting-point metal fusion-bonded iron-air battery negative electrode provided by the present invention is a bismuth or bismuth alloy that expands in volume when solidified. After melting, it solidifies, and the volume expansion of the solidified solid is constrained by the skeleton formed by the iron-based active particles and is converted into internal pressure, forming a press-fit mechanical lock on the iron-based active particles. The bismuth is pure bismuth with a purity of not less than 99 wt%, and the bismuth alloy is a bismuth-tin alloy with a tin content of not more than 42 wt% and a melting point of 138–271.4 °C. The low-melting-point metal-bonded conductive phase is an independent pure metal phase, and there are no intermetallic compounds between it and the iron-based active particles.
[0013] The low-melting-point metal fusion bonded iron-air battery negative electrode provided by the present invention has a content of 5-25 wt% of the low-melting-point metal bonded conductive phase based on the total mass of the active layer; and a porosity of 20%-38% for the active layer.
[0014] The low-melting-point metal-fused-bonded iron-air battery negative electrode provided by the present invention comprises iron-based active particles that are one of carbonyl iron powder, reduced iron powder, or a mixture thereof; the iron content of the carbonyl iron powder is not less than 99.5 wt%. According to the low melting point metal fusion bonded iron-air battery negative electrode provided by the present invention, the active layer further includes anti-passivation additive particles, wherein the anti-passivation additive particles are one or more of ferrous sulfide, ferrous disulfide, zinc sulfide, sodium sulfide, and potassium sulfide; the content of the anti-passivation additive particles is 3 to 15 wt% based on the total mass of the active layer.
[0015] According to the present invention, the low melting point metal fusion bonded iron-air battery negative electrode further includes a current collector, the active layer is composited on at least one surface of the current collector, and the continuous three-dimensional metal network anchors the active layer to the surface of the current collector. The current collector is a nickel-plated copper mesh, nickel mesh, nickel sheet, nickel foam, stainless steel mesh, or iron mesh. Alternatively, the negative electrode is a self-supporting electrode without current collectors, which maintains the mechanical integrity of the active layer by relying on the continuous three-dimensional metal network, and draws out the current through metal current drawers embedded or welded to the active layer.
[0016] A method for preparing a low-melting-point metal molten bonded iron-air battery negative electrode as described in any of the preceding claims is provided, comprising the following steps: Step 1: Dry mix the raw material powder, including iron-based active powder and low-melting-point metal powder, to obtain a mixed powder. Step 2: The mixed powder is spread on at least one surface of the current collector, or the mixed powder is filled into the cavity of the hot press mold; Step 3: Heat to a temperature 10-50°C higher than the melting point of the low-melting-point metal, apply a pressure of 10-500 MPa and hold for 3-15 minutes, so that the molten low-melting-point metal wets the particle surface of the iron-based active powder and fills the gaps between the particles. Step four: Under the condition of maintaining auxiliary pressure, the temperature is reduced to below the melting point of the low melting point metal at a rate of 1-5℃ / min, so that the low melting point metal solidifies, cools and demolds to obtain the negative electrode of the iron-air battery.
[0017] An iron-air battery is provided, comprising the aforementioned low-melting-point metal molten bonded iron-air battery negative electrode, a bifunctional air positive electrode, a separator, and an alkaline electrolyte; wherein the alkaline electrolyte is a potassium hydroxide aqueous solution with a mass concentration of 10% to 35%.
[0018] As mentioned above, iron-air batteries are used in grid energy storage, renewable energy power generation supporting energy storage, or backup power systems.
[0019] The low-melting-point metal molten bonded iron-air battery negative electrode, its preparation method, and its application provided by this invention have the following beneficial effects: (1) Traditional negative electrodes must add insulating polymer binders and carbon conductive agents, and the inert components crowd out the proportion of active materials. This invention relies on the formation of a continuous metal network by melting low-melting-point metals to replace the two types of inert additives, significantly increasing the proportion of iron-based active materials and improving the electrode energy density.
[0020] (2) Reduced internal resistance and long-term stable conductivity: Polymers form insulating pathways inside the electrode, and carbon conductive agents are prone to oxidation and loss during long-term cycling. The three-dimensional metal bridging network of this invention constructs a continuous conductive channel throughout the entire domain, which greatly reduces the ohmic internal resistance of the electrode, while eliminating the risk of carbon material oxidation failure, resulting in lower energy loss during charging and discharging.
[0021] (3) High mechanical strength and flexible structure of the electrode: Traditional electrodes rely solely on polymer bonding, which is prone to powder shedding and falling off, and must be matched with a current collector. The present invention preferably uses a bismuth / bismuth alloy to utilize solidification expansion for self-tightening and locking, and the particles, active layer and current collector are firmly bonded; it can also prepare a self-supporting electrode without a current collector, which is suitable for the processing of thick plates and large-size energy storage electrodes, and is not prone to cracking during assembly and cycling.
[0022] (4) High charging efficiency and no activation period loss: Existing technologies use precursor additives such as bismuth oxide, which require multiple charge-discharge cycles to activate and suppress hydrogen evolution, resulting in significant efficiency loss in the early stages. This invention directly uses elemental low-melting-point metal to form a mold, suppressing hydrogen evolution during charging across the entire process. Stable charging efficiency can be achieved in the first cycle, with no activation power loss.
[0023] (5) Suppressing discharge passivation and extending cycle life: Traditional negative electrodes are prone to forming a dense insulating passivation film, resulting in high-rate capacity decay and continuous decline in long-term cycle capacity. This invention can add sulfide anti-passivation additives to the electrode or supplement sulfur components in the electrolyte to alleviate passivation and inert oxide accumulation, thereby simultaneously improving rate performance and cycle stability.
[0024] (6) Simple process and easy to mass-produce, suitable for multiple energy storage scenarios: Traditional electrode formulations have many components and limited molding processes. The dry mixing and hot-pressing process of this invention is simple, with a wide process window and compatibility with a variety of low-cost current collectors; the iron-air battery equipped with this negative electrode is safe and environmentally friendly, with a long discharge time, and can be adapted to various long-term energy storage scenarios such as grid energy storage, new energy supporting energy storage, and backup power. Attached Figure Description
[0025] To more clearly illustrate the technical solutions in this invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0026] Figure 1This is a schematic cross-sectional view of the low-melting-point metal molten bonded iron air battery negative electrode, its preparation method, and its application provided in the embodiments of the present invention. Figure 2 This is a schematic diagram of the solidification self-tightening effect of low-melting-point metal (taking solidification-expansion type bismuth as an example) in the low-melting-point metal molten bonded iron-air battery negative electrode and its preparation method and application provided in the embodiments of the present invention. (a) is the liquid metal filling stage, (b) is the solidification front advancement stage, and (c) is the solidification expansion self-tightening locking stage. Figure 3 This is a process flow diagram of the preparation method of the low melting point metal fusion bonded iron-air battery negative electrode and its preparation method and application provided in the embodiments of the present invention. Figure 4 This is a schematic diagram of the temperature-pressure time series curve of the hot pressing process of the low melting point metal molten bonded iron-air battery negative electrode and its preparation method and application provided in the embodiments of the present invention; Figure 5 This is a curve showing the effect of bismuth content on the porosity of the active layer and the 90° peel strength on the low melting point metal fusion bonded iron-air battery anode and its preparation method and application provided in the embodiments of the present invention. Figure 6 This is a curve showing the effect of bismuth content on charging efficiency and 1C specific capacity of the low melting point metal fusion bonded iron-air battery negative electrode, its preparation method and application provided in the embodiments of the present invention. Figure 7 This is a curve showing the effect of ferrous sulfide content on 3C specific capacity and charge transfer resistance at the end of discharge of the low melting point metal molten bonded iron-air battery negative electrode and its preparation method and application provided in the embodiments of the present invention. Figure 8 This invention provides a comparison curve of the charging efficiency of the low-melting-point metal molten bonded iron-air battery negative electrode and its preparation method and application in the first 10 cycles of the scheme of directly adding low-melting-point metal elemental powder and Bi2O3 precursor. Figure 9 This is a comparison curve of the capacity retention rate after 500 cycles between the embodiment and the comparative example of the low melting point metal molten bonded iron-air battery negative electrode, its preparation method and application provided in this invention. Figure 10 This is a graph showing the improvement in overall performance of Example 2 (polymer-bonded electrode) of the low-melting-point metal fusion bonded iron-air battery anode and its preparation method and application provided in this invention, compared to Comparative Example 1.
[0027] Figure label: 100. Iron-air battery negative electrode; 1. Current collector; 11. Copper mesh substrate; 12. Nickel plating; 2. Iron-based active particles; 3. Low-melting-point metal bonded conductive phase; 31. Low-melting-point metal necking bridging structure; 4. Anti-passivation additive particles; 5. Connecting pores. Detailed Implementation
[0028] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.
[0029] Therefore, the following detailed description of the embodiments of the invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the invention without inventive effort are within the scope of protection of the invention.
[0030] It should be noted that similar reference numerals and letters in the following figures indicate similar items; therefore, once an item is defined in one figure, it does not need to be further defined and explained in subsequent figures. Furthermore, the terms "first," "second," etc., are used only to distinguish descriptions and should not be construed as indicating or implying relative importance.
[0031] In the description of the embodiments of the present invention, it should be noted that the terms "inner", "outer", "upper", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, or the orientation or positional relationship in which the product of the invention is usually placed when in use. They are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limiting the present invention.
[0032] This application provides a low-melting-point metal fusion-bonded iron-air battery negative electrode 100. The negative electrode includes an active layer comprising iron-based active particles 2 and a low-melting-point metal-bonded conductive phase 3. The active layer does not contain polymer binders or carbon-based conductive agents. The low-melting-point metal-bonded conductive phase 3 is a continuous three-dimensional metal network formed by a melting-solidification process of a low-melting-point metal with a melting point of 130-350°C. The continuous three-dimensional metal network forms a bridging structure at the contact necks of adjacent iron-based active particles 2, bonding the iron-based active particles 2 together and forming a continuous electron conduction pathway within the active layer. The content of the low-melting-point metal-bonded conductive phase 3 is 5-25 wt% based on the total mass of the active layer.
[0033] The working principle of fusion bonding: At a temperature higher than the melting point of the low-melting-point metal, liquid metal, driven by pressure, wets and fills the contact neck of adjacent iron particles. In the embodiment using current collector 1, it simultaneously wets and fills the interface between the active layer and current collector 1. After solidification, it forms a continuous metal network that covers and bridges the neck and runs through the entire electrode, such as... Figure 1 As shown, this invention provides both strong mechanical bonding between particles (and between particles and current collector 1) and a continuous electronic conduction pathway without the use of polymer binders or carbon-based conductive agents. Unlike existing iron electrode solutions that use oxides / sulfides of bismuth, tin, etc., as small additives and have molding temperatures below the metal's melting point, and also unlike liquid metal battery solutions where the metal is in a liquid state and serves as the active material during battery operation, in this invention, the low-melting-point metal only melts briefly during the preparation stage and remains solid throughout the battery's service temperature, stably existing as an electrochemically inert structural binder and conductive phase.
[0034] The low-melting-point metal is bismuth, tin, or lead, or an alloy containing at least one of bismuth, tin, or lead.
[0035] The low-melting-point metal is bismuth or a bismuth alloy that expands in volume upon solidification. After melting, it solidifies, and the volume expansion of the solidified solid is constrained by the skeleton formed by the iron-based active particles 2 and is converted into internal pressure, forming a press-fit mechanical lock on the iron-based active particles 2. The bismuth is pure bismuth with a purity of not less than 99 wt%, and the bismuth alloy is a bismuth-tin alloy with a tin content of not more than 42 wt% and a melting point of 138–271.4 °C. The low-melting-point metal-bonded conductive phase 3 is an independent pure metal phase, and there are no intermetallic compounds between it and the iron-based active particles 2.
[0036] Specifically, among the available low-melting-point metals, this invention preferably uses bismuth and bismuth alloys, which expand in volume upon solidification. Bismuth is one of the very few metals that expands in volume upon solidification (approximately +3.32%). When it solidifies within a rigid iron particle skeleton, the constrained volume expansion is converted into internal pressure, forming a press-fit mechanical lock on the contact neck of the iron particles (and the surface of current collector 1), i.e., the "solidification self-tightening effect." Figure 2As shown, a peel strength approximately 37% higher than that of polymer-bonded electrodes is achieved without the use of any polymer binders. Simultaneously, the iron-bismuth binary system exhibits extremely low miscibility at atmospheric pressure and does not form intermetallic compounds (even at 1873 K in liquid form, the solubility of bismuth in iron is only about 0.16 wt%, and no stable Fe-Bi intermetallic compounds have been found at atmospheric pressure to date). After solidification, bismuth exists stably as an independent pure metallic phase, thus enabling it to simultaneously perform three functions: (a) bonding – solidification self-tightening mechanical locking; (b) conductivity – a continuous bismuth metal network (with a conductivity of approximately 8.7 × 10⁵ S / m, about 19 orders of magnitude higher than that of polymers) replaces the combination of "polymer insulating network + carbon conductive agent," reducing the electrode's ohmic resistance by approximately 27%; (c) hydrogen evolution suppression – bismuth is located at the end of the weak hydrogen adsorption branch in the alkaline hydrogen evolution volcano diagram, and its intrinsic hydrogen evolution exchange current density is 2–3 orders of magnitude lower than that of iron, significantly suppressing the hydrogen evolution side reaction during charging. As a result, the electrode formulation has been simplified from five to six components in the existing technology to two to three components, and the proportion of active components has been increased from about 73% to about 85%.
[0037] Regarding the specific selection of low-melting-point metals, bismuth, tin, lead, and alloys containing at least one of these elements (such as bismuth-tin alloys, tin-lead alloys, bismuth-lead alloys, and bismuth-tin-lead alloys) can all form continuous metal networks and achieve binder-free molding based on the same melt-bonding principle. Bismuth is a solidification-expanding metal, possessing the triple advantages of solidification self-tightening, high hydrogen evolution overpotential, and no formation of iron-based intermetallic compounds, making it the optimal choice due to its superior overall performance. Tin has a low melting point (231.9℃), lower raw material costs, and a volume shrinkage of approximately 2.8% during solidification. It has no self-tightening effect, but the thin layer of FeSn2 intermetallic compound formed between tin and iron at the interface can provide metallurgical bonding, still enabling the formation of a continuous bond. For conductive networks, tin has a lower hydrogen evolution overpotential than bismuth, resulting in a slightly lower charging efficiency. It is suitable for applications sensitive to hot-pressing temperature and cost, with moderate performance requirements. Lead has a melting point of 327.5℃, shrinks in volume by about 3.5% upon solidification, and has no self-tightening effect. However, lead has one of the highest intrinsic hydrogen evolution overpotentials among commonly used metals, significantly inhibiting hydrogen evolution. Furthermore, it maintains metallic stability in the iron negative electrode working potential region in alkaline electrolytes, making it suitable for applications requiring high charging efficiency. When selecting lead, environmental regulations in the region must be met. Tin-lead alloys (such as Sn63Pb37 eutectic, with a melting point of approximately 183℃) and bismuth-lead alloys offer flexibility in balancing melting point, cost, and electrochemical performance. Overall, bismuth with solidification expansion and bismuth-rich alloys offer the best comprehensive performance.
[0038] The low-melting-point metal must meet two basic conditions: first, its melting point must be significantly lower than that of iron, so that it can melt and fill at a temperature that does not damage the active iron material; second, after solidification, it must remain solid at the operating temperature of the iron negative electrode to maintain the mechanical stability of the bonded network. Accordingly, the melting point range is limited to 130–350°C: the lower limit of 130°C ensures that the bonded network remains solid and does not soften or remelt at the battery service temperature (including self-heating and high-temperature environments, typically not exceeding approximately 60–80°C) (for example, bismuth indium tin alloy with a melting point of 62°C may soften at service temperature and is therefore not within the scope of this invention); the upper limit of 350°C takes into account energy consumption and covers the melting points of bismuth (271.4°C) and lead (327.5°C), while excluding conventional structural metals. Low-melting-point metals that meet this condition include, but are not limited to, bismuth, tin, lead, and alloys containing at least one of bismuth, tin, and lead (such as bismuth-tin alloys, tin-lead alloys, and bismuth-lead alloys), as well as other low-melting-point metals such as indium that meet the above melting point conditions. Since the wetting-filling-solidification bonding of liquid metal to iron particles follows the same physical mechanism, all of the above metals can be formed into a continuous metal network by the process of this invention to achieve binder-free molding.
[0039] Taking randomly packed carbonyl iron spherical particles (porosity approximately 36%) as an example, after density conversion, approximately 41 wt% of bismuth is required to completely fill the interparticle gaps. At this point, the porosity approaches zero, and electrolyte transport is impossible. To retain 20%–38% (preferably 25%–35%) of connected pores to ensure hydroxide ion transport, the upper limit of the metal mass fraction is approximately 22–25 wt%. Regarding the lower limit, the metal amount needs to be sufficient to cover the contact necks between particles to form a continuous bonding network. The required metal amount is related to the ratio of the metal powder particle size to the iron particle size: when using conventional particle size metal powder (D50 approximately 10–20 μm), the lower limit is approximately 10–12 wt%; when using fine particle size metal powder (D50 not greater than 10 μm) and combined with higher hot-pressing pressure, the fine powder preferentially aggregates towards the contact neck under capillary force, and 5–10 wt% can form an effective neck bridging, suitable for thin electrodes and shallow cycling scenarios. Experiments have confirmed that… Figure 5-6 As shown, the optimal window for overall performance is around 15wt%. At this content, the continuous conductive network and bonding strength are fully established, while maintaining a higher proportion of active material and a higher interconnectivity of pores, and significantly reducing the amount of bismuth used and the cost of raw materials; when the content is not less than 15wt%, the peel strength is not less than 15N / cm.
[0040] Based on the total mass of the active layer, the content of the low-melting-point metal-bonded conductive phase 3 is 5-25 wt%, more preferably 15 wt%; the porosity of the active layer is 20%-38%.
[0041] Pure bismuth has a melting point of 271.4℃ and a solidification expansion of approximately +3.32%, exhibiting the strongest self-tightening effect and providing the best overall combination of hydrogen evolution suppression and mechanical strength. Bismuth-tin alloys (such as Bi58Sn42 eutectic, with a melting point of approximately 138℃) can significantly reduce hot-pressing temperatures, thereby significantly reducing equipment requirements and energy consumption. However, the solidification expansion of the bismuth-rich phase is less than that of pure bismuth, and the self-tightening effect is slightly weaker. Furthermore, the hydrogen evolution overpotential of tin is lower than that of bismuth. Therefore, the tin content in the alloy should preferably not exceed 42wt% (eutectic composition).
[0042] The iron-based active particles 2 are one of carbonyl iron powder, reduced iron powder, or a mixture thereof; the iron content of the carbonyl iron powder is not less than 99.5 wt%; the iron-based active particles 2 are dispersed in a continuous three-dimensional metal network composed of a low-melting-point metal-bonded conductive phase 3, and the contact necks of adjacent iron particles 2 form a low-melting-point metal neck-covered bridging structure 31.
[0043] It should be noted that carbonyl iron powder (spherical, D50 of 1-50 μm, preferably 1-10 μm, iron content not less than 99.5 wt%) has the best performance due to its spherical morphology, which is conducive to uniform stacking and the formation of regular contact necks. Its high purity can avoid self-discharge and side reactions introduced by impurities. Reduced iron powder is inexpensive and can be used alone or mixed with carbonyl iron powder to reduce raw material costs. Its particle size is larger (D50 can reach 45 μm) and its purity is slightly lower (about 98.5 wt%), resulting in a slight decrease in charging efficiency and rate performance. It is suitable for cost-sensitive scenarios with moderate performance requirements. When using a mixture of carbonyl iron powder and reduced iron powder, the proportion of reduced iron powder should preferably not exceed 25 wt% to balance cost and performance.
[0044] The active layer also includes anti-passivation additive particles 4, which are one or more of ferrous sulfide, ferrous disulfide, zinc sulfide, sodium sulfide, and potassium sulfide; the content of the anti-passivation additive particles 4 is 3 to 15 wt% based on the total mass of the active layer.
[0045] Specifically, the active layer includes anti-passivation additive particles 4, with a content of 3-15 wt% based on the total mass of the active layer. The anti-passivation additive slowly releases sulfur species in the electrolyte, adsorbs onto the surface of iron particles, and participates in the interfacial phase composition, preventing the formation of a dense passivation film from discharge products and inhibiting the accumulation of inactive phases. The anti-passivation additive can be selected from one or more of ferrous sulfide, ferrous disulfide, zinc sulfide, sodium sulfide, and potassium sulfide: ferrous sulfide is a solid-phase slow-release type, its dissolution is thermodynamically limited, its release is stable, and the dissolved iron ions do not introduce foreign impurities, making it the optimal choice; zinc sulfide has coulombic efficiency and rate capability comparable to ferrous sulfide; sodium sulfide and potassium sulfide have high solubility and rapid release, and are suitable for use in combination with ferrous sulfide at a lower ratio, or as an electrolyte sulfur replenishment additive. When the content is below 3wt%, the anti-passivation effect is insufficient; usually around 5wt% can play an effective anti-passivation role. Higher contents tend to slow down the performance gain and crowd out the proportion of active material, so 3-8wt% is preferred, and 5wt% is even more preferred.
[0046] It should be noted that the functions of the anti-passivation additive and the low-melting-point metal binder conductive phase 3 are orthogonal: the low-melting-point metal mainly solves the problems of electrode structural bonding, conductivity, and hydrogen evolution suppression at the charging end, while the anti-passivation additive mainly solves the passivation problem at the discharging end. Therefore, the anti-passivation additive is an optional component: without the anti-passivation additive, the active layer consists only of iron-based active particles 2 and low-melting-point metal binder conductive phase 3, which can still be normally melted and bonded to form a continuous conductive network and obtain high charging efficiency. It is suitable for application scenarios such as low-rate long-term energy storage where high-rate discharge performance requirements are not high, or it can be used in conjunction with an electrolyte sulfur replenishment scheme, where the electrolyte provides the sulfur species required to suppress passivation; with the anti-passivation additive, the high-rate discharge capacity and cycle stability of the electrode are significantly improved, making it suitable for application scenarios with high requirements for rate performance.
[0047] The negative electrode also includes a current collector 1, the active layer is composited on at least one surface of the current collector 1, and the continuous three-dimensional metal network anchors the active layer to the surface of the current collector 1. The current collector 1 is a nickel-plated copper mesh, nickel mesh, nickel sheet, nickel foam, stainless steel mesh, or iron mesh. Alternatively, the negative electrode is a self-supporting electrode without current collector 1, which maintains the mechanical integrity of the active layer by relying on the continuous three-dimensional metal network, and draws out the current through a metal current drawer embedded or welded to the active layer.
[0048] Specifically, the negative electrode also includes a current collector 1, the active layer being laminated onto at least one surface of the current collector 1, and the continuous three-dimensional metal network anchoring the active layer to the surface of the current collector 1. The current collector 1 can be a nickel-plated copper mesh, nickel mesh, nickel sheet, nickel foam, stainless steel mesh, or iron mesh. Low-melting-point metals such as liquid bismuth have excellent wettability on nickel surfaces (contact angle approximately 25–45°), and nickel is in the thermodynamically stable region of the iron negative electrode working potential in alkaline electrolytes. All of the above-mentioned nickel-based current collectors 1 are compatible with the fusion bonding process of this invention. Among them, the nickel-plated copper mesh is preferred, combining the high conductivity of the copper substrate with the alkali resistance of the nickel surface. The preferred mesh size for the copper mesh substrate 11 is 60–200 mesh, and the preferred nickel plating layer 12 thickness is 5–30 μm. The three-dimensional porous structure of the nickel foam is beneficial for powder anchoring of thick electrodes and can be selected according to the application scenario. Stainless steel mesh (such as 304 and 316L stainless steel wire woven mesh) is in the passivation and stability zone of the iron negative electrode working potential area in alkaline electrolyte. It has high mechanical strength and its cost is significantly lower than that of nickel-based current collector 1. Under hot pressing conditions in a hydrogen-containing reducing atmosphere, liquid low-melting-point metal can effectively wet and anchor its surface. The iron mesh and iron-based active particles 2 are homogeneous, and there is no dissimilar metal contact interface. Its surface oxide film is reduced simultaneously with the iron powder surface oxide film in a hydrogen-containing reducing atmosphere. Liquid bismuth has excellent wettability on fresh iron surfaces, and its raw material cost is the lowest among all current collectors 1, making it particularly suitable for cost-sensitive long-term energy storage scenarios. When current collector 1 is used and the content of low-melting-point metal bonding conductive phase 3 is not less than 15wt%, the 90° peel strength between the active layer and current collector 1 is not less than 15N / cm.
[0049] The negative electrode is a self-supporting electrode without current collector 1: Since the continuous three-dimensional metal network runs through the entire active layer, it provides sufficient mechanical strength to maintain its structural integrity. Therefore, the mixed powder can be directly filled into the hot-pressing mold cavity and integrally formed into a plate-shaped self-supporting electrode through melting and solidification. Current is then drawn out through metal current-draining components (such as nickel strips or nickel sheets) pre-embedded or welded to the active layer. The self-supporting solution eliminates the non-active component current collector 1, further reducing electrode mass and material costs, and simplifying the electrode structure. It is particularly suitable for thick plate electrodes and cost-sensitive long-term energy storage scenarios. The thickness of the self-supporting electrode is preferably 0.5–3 mm. Therefore, current collector 1 is an optional component in this invention and can be flexibly selected based on electrode thickness, mechanical strength requirements, and cost objectives.
[0050] Preferably, the low-melting-point metal-bonded conductive phase 3 is an independent pure metal phase, with no intermetallic compounds between it and the iron-based active particles 2. The continuous three-dimensional metal network forms a continuous electronic conduction pathway inside the active layer to ensure the chemical and structural stability of the binder phase during long-term cycling.
[0051] A method for preparing the low-melting-point metal fusion-bonded iron-air battery negative electrode 100 as described in any of the preceding claims is provided, comprising the following steps: Step 1: Iron-based active powder (one of carbonyl iron powder, reduced iron powder or a mixture thereof), low-melting-point metal powder (preferably bismuth powder or bismuth alloy powder), and anti-passivation additive powder added as needed are mixed in proportion under a protective atmosphere using a V-type mixer or a double cone mixer for 20-60 minutes to obtain a mixed powder; the dry mixing process can avoid the segregation of high-density metal powder during the mixing process.
[0052] Step 2: The mixed powder is evenly spread on at least one surface of the current collector; or, when preparing the self-supporting negative electrode, the mixed powder is directly filled into the cavity of the hot press mold and leveled, and metal guides are pre-embedded at the edge of the powder layer if necessary.
[0053] Step 3: In a hydrogen-containing reducing atmosphere (nitrogen gas containing 2%–10% hydrogen by volume), heat the current collector (or the mold containing the mixed powder) coated with the powder to a temperature 10–50°C higher than the melting point of the low-melting-point metal used (280–320°C for pure bismuth, 150–220°C for bismuth-tin alloy, 242–282°C for tin, and 338–378°C for lead), and apply a pressure of 10–500 MPa for hot pressing and hold for 3–15 minutes. This allows the molten liquid metal to wet the surface of the iron particles and fill the gaps between them. Preferably, a pre-pressure of 3–6 MPa is applied at a temperature lower than the metal's melting point, and the pressure is increased to the target pressure of 10–500 MPa after the metal has completely melted. This prevents the powder from being dispersed by high pressure in an unbonded state. Maintain a slightly positive pressure in the reducing atmosphere throughout the hot pressing process to reduce the oxide film on the iron powder surface and restore the wettability of the liquid metal on the iron particle surface.
[0054] Step four: While maintaining auxiliary pressure, the temperature is lowered at a rate of 1–5 °C / min to below the melting point of the low-melting-point metal used, causing the metal to solidify. When solidification expansion-type bismuth or bismuth alloys are used, the solidification volume expansion is converted into interparticle locking pressure to achieve self-tightening. Subsequently, cooling and demolding are performed to obtain the iron-air battery negative electrode. Controlled cooling and auxiliary pressure ensure that solidification expansion is converted into interparticle locking pressure rather than interlayer cracking.
[0055] The preferred molds for hot pressing are graphite molds or metal molds with nitriding or ceramic coating to avoid the embrittlement effect of liquid metal on stressed steel molds. When the hot pressing pressure exceeds 50 MPa (especially when using high-pressure schemes up to 500 MPa), the strength of graphite molds is insufficient, and high-strength alloy steel molds with nitriding or ceramic coating should be used.
[0056] The hot pressing is preferably carried out in a hydrogen-containing reducing atmosphere: the hydrogen-containing reducing atmosphere reduces the oxide film on the surface of the iron powder to a fresh metal surface at the hot pressing temperature, restoring the wettability of the liquid metal to the iron particles (the contact angle of the iron surface with an oxide film to liquid bismuth, etc., is greater than 90° and it is not wetted), which can significantly improve the quality of melt bonding. When the surface oxidation degree of the iron-based active powder is low or it has been pre-reduced, hot pressing can also be carried out in an inert atmosphere such as nitrogen or argon. In addition, when using low-melting-point metal elemental powder (rather than its oxide / sulfide precursor), the metal is in a thermodynamically final state from the time of addition, and can achieve high charging efficiency on the first charge, eliminating the need for the multiple in-situ reduction and activation process required by existing precursor schemes, that is, it has the characteristic of "zero activation period".
[0057] An iron-air battery includes an iron-air battery negative electrode 100, a bifunctional air positive electrode, a separator, and an alkaline electrolyte; the alkaline electrolyte is a potassium hydroxide aqueous solution with a mass concentration of 10% to 35%. The electrolyte may also contain 0.5 to 5 mmol / L of potassium sulfide or sodium sulfide as a sulfur replenishment additive to continuously replenish sulfur species during cycling and extend cycle life; when the active layer does not contain a solid-phase anti-passivation additive, the sulfur species required to suppress passivation can also be provided solely by the electrolyte sulfur replenishment scheme.
[0058] As mentioned above, iron-air batteries are used in grid energy storage, renewable energy power generation supporting energy storage, or backup power systems.
[0059] To more clearly and in detail introduce the low-melting-point metal fusion bonded iron-air battery negative electrode, its preparation method, and its application provided by the embodiments of the present invention, the following description will be based on specific embodiments.
[0060] Example 1
[0061] Two-component negative electrode with 12wt% bismuth content and no passivation additives: Step 1: Weigh out 88wt% carbonyl iron powder and 12wt% bismuth powder, place them in a V-type mixer and dry mix at 30r / min for 30min under argon protection.
[0062] Step 2: Evenly spread the mixed powder on both sides of a 5cm×5cm nickel-plated copper mesh, with a density of approximately 60mg / cm² on one side. 2 .
[0063] Step 3: Place the powdered current collector into a graphite mold, put it into an atmosphere hot press, introduce a nitrogen / 5% hydrogen mixture and maintain a slight positive pressure; increase the temperature at 5℃ / min, apply a pre-pressure of 5MPa at 200℃; after heating to 295℃ (when bismuth is completely melted), increase the pressure to 15MPa and hold the pressure for 8min.
[0064] Step 4: Cool to 250℃ at 3℃ / min (maintaining an auxiliary pressure of 5MPa), and demold after cooling to room temperature in the furnace. The measured porosity of the active layer is 34.8%, the 90° peel strength is 9.8N / cm, the sheet resistance is 11.5mΩ / □, and the electrode is well formed, proving that the two-component active layer can be normally melt-bonded and formed.
[0065] Example 2
[0066] Bismuth content 15wt% The ratio is 80wt% carbonyl iron powder, 15wt% bismuth powder, and 5wt% ferrous sulfide powder, with the remaining processes being the same as in Example 1.
[0067] This formulation increases the proportion of active material while ensuring a continuous conductive network and bonding strength, and significantly reduces bismuth usage and raw material costs. Measured porosity is 31.2% ± 1.5%, peel strength is 15.4 ± 1.0 N / cm, and sheet resistance is 9.6 mΩ / □.
[0068] Electrochemical performance (three-electrode system, Hg / HgO reference, 30wt% potassium hydroxide, 25℃, evaluated after 20 cycles of C / 5 activation): specific capacity C / 5: 0.32 Ah / g, 1C: 0.278±0.009 Ah / g, 3C: 0.183±0.012 Ah / g; electrode internal resistance in ohms: approximately 17.1 mΩ; capacity retention after 500 cycles of 100% depth charge-discharge: 91.3%. Figure 9 As shown. The charging efficiency approaches a stable level in the first cycle and remains stable from the third cycle onwards, exhibiting zero activation period characteristics. Figure 8 X-ray diffraction after cycling showed that the position and intensity of the bismuth characteristic peaks remained basically unchanged, and no bismuth oxide diffraction peaks appeared; scanning electron microscopy showed that the neck-coated bridging structure 31 was intact and without cracks; inductively coupled plasma atomic emission spectrometry (ICP-AES) analysis did not detect measurable bismuth dissolution in the electrolyte, proving that the bismuth binder phase is stable in alkaline cycling for a long time. Replacing the ferrous sulfide powder in this embodiment with an equal mass of zinc sulfide powder (5wt%), the rate performance and cycle stability of the resulting electrode were comparable to those of the ferrous sulfide scheme, and zinc sulfide can be used as an effective substitute for anti-passivation additives.
[0069] Example 3
[0070] Mixed iron powder and pure reduced iron powder: The proportions are 62 wt% carbonyl iron powder, 15 wt% reduced iron powder, 18 wt% bismuth powder, and 5 wt% ferrous sulfide powder (reduced iron powder accounts for approximately 19.5 wt% of the total mass of iron-based active particles), and the remaining processes are the same as in Example 1.
[0071] The 1C specific capacity is 0.261 Ah / g, and the capacity retention rate after 500 cycles is 89.5%. The formulation consists of 77 wt% reduced iron powder, 18 wt% bismuth powder, and 5 wt% ferrous sulfide powder (all iron-based active particles are reduced iron powder). Due to the large particle size and thick surface oxide film of the reduced iron powder, the hot pressing holding time was extended to 12 min, and the hydrogen content of the reducing atmosphere was increased to 8% by volume to fully reduce the surface oxide film. The resulting electrode has a peel strength of 15.8 N / cm, a 1C specific capacity of 0.243 Ah / g, and a capacity retention rate of 87.8% after 500 cycles.
[0072] The above results indicate that iron-based active particles can be a mixture of carbonyl iron powder and reduced iron powder, or they can be entirely reduced iron powder. Using reduced iron powder can reduce raw material costs by about 20% to 35%. Its charging efficiency and rate performance are slightly reduced due to the larger particle size and slightly lower purity of reduced iron powder. It is suitable for cost-sensitive scenarios with moderate performance requirements.
[0073] Example 4
[0074] The process parameters differed from those in Example 2, with the same formulation: (a) at a hot-pressing temperature of 285°C, the coarser bismuth particles did not melt completely, resulting in a peel strength of only 8.2 N / cm; (b) at 315°C, the viscosity of the liquid bismuth further decreased, leading to edge overflow under high pressure, with porosity dropping to 24.1% and IC capacity decreasing to 0.248 Ah / g; (c) at a pressure of 10 MPa, penetration was insufficient (peel strength 10.3 N / cm); (d) at a pressure of 20 MPa, excessive bismuth was observed in the formulation of Example 2 (bismuth content 15 wt%). (e) Reducing the bismuth content to 8 wt% (87 wt% carbonyl iron powder, 8 wt% bismuth powder, 5 wt% ferrous sulfide powder), using a high-strength alloy steel mold with surface nitriding treatment, and increasing the pressure to 500 MPa, the iron particle skeleton undergoes local plastic deformation, and the contact area between particles significantly increases. The measured porosity is 23.6%, the peel strength is 19.2 N / cm, and the 1C specific capacity is 0.258 Ah / g. The electrode density and mechanical strength are significantly improved. It can be seen that the optimal process window for the conventional pure bismuth scheme is 290–305℃ and 13–17 MPa. Figure 4-6 As shown, with a reduction in bismuth content, the hot-pressing pressure can be increased to a maximum of 500 MPa.
[0075] Example 5
[0076] Low-temperature variants of bismuth-tin alloys: The pure bismuth powder in Example 2 was replaced with an equal mass of Bi58Sn42 eutectic alloy powder (melting point approximately 138°C), and the hot pressing temperature was correspondingly reduced to 165°C, while the rest of the process remained unchanged.
[0077] The resulting electrode has a peel strength of 14.6 N / cm (the solidification expansion of the eutectic alloy is less than that of pure bismuth, and the self-tightening effect is slightly weaker but still significant), and a 1C specific capacity of 0.266 Ah / g.
[0078] Using a bismuth-tin alloy can reduce the hot pressing temperature by about 130°C, significantly reducing equipment requirements and energy consumption. The slight impact on charging efficiency is due to the fact that the hydrogen evolution overpotential of tin is lower than that of bismuth, so the tin content in the alloy should not exceed 42 wt% (eutectic composition).
[0079] Example 6
[0080] Bismuth content 5wt%, fine bismuth powder thin electrode: Fine-grained bismuth powder (D50 approximately 5 μm, comparable to carbonyl iron powder particle size) was used, with a ratio of 90 wt% carbonyl iron powder, 5 wt% fine bismuth powder, and 5 wt% ferrous sulfide powder; the single-sided density was reduced to 30 mg / cm³. 2 (Thin electrode), hot pressing pressure increased to 18MPa, the rest of the process is the same as in Example 1.
[0081] After melting, the fine bismuth powder preferentially aggregates towards the particle contact neck under capillary force. Scanning electron microscopy confirmed the formation of discontinuous bridging points that cover the main contact neck. The measured peel strength is 7.2 N / cm, porosity is 37.5%, and 1C specific capacity is 0.262 Ah / g.
[0082] Under the conditions of fine bismuth powder, thin electrodes, and high voltage, 5wt% bismuth can achieve effective bonding and molding; this solution is suitable for thin, shallow-cycle battery scenarios with high requirements for porosity and active material content, and moderate mechanical strength.
[0083] Example 7
[0084] Pure nickel mesh, stainless steel mesh and iron mesh current collectors: Replace the nickel-plated copper mesh in Example 2 with a 200-mesh pure nickel mesh, while keeping the rest of the process unchanged.
[0085] Liquid bismuth wets nickel surfaces well, and the resulting electrode has a peel strength of 16.0 N / cm (comparable to nickel-plated copper mesh), an electrode internal resistance of about 19.5 mΩ (higher than the 17.1 mΩ of nickel-plated copper mesh, due to the lower conductivity of nickel compared to copper, but still significantly lower than the 23.5 mΩ of the polymer bonding control), and a 1C specific capacity of 0.272 Ah / g.
[0086] Further, the current collectors were replaced with 100-mesh 316L stainless steel mesh and 80-mesh low-carbon steel mesh, respectively, while the other processes remained unchanged. The stainless steel mesh solution showed a peel strength of 15.3 N / cm, an electrode ohmic resistance of approximately 20.8 mΩ, and a 1C specific capacity of 0.266 Ah / g. This indicates that liquid bismuth can effectively wet and anchor on the stainless steel surface under hot-pressing conditions in a hydrogen-containing reducing atmosphere, and the stainless steel mesh maintains passivation stability in the iron negative electrode working potential region in an alkaline electrolyte. In the iron mesh solution, the oxide film on the iron mesh surface was simultaneously reduced with the oxide film on the iron powder surface in a hydrogen-containing atmosphere, and the liquid bismuth fully wetted the fresh iron surface, achieving a peel strength of 16.6 N / cm, an electrode ohmic resistance of approximately 19.9 mΩ, and a 1C specific capacity of 0.268 Ah / g. Furthermore, the iron mesh and active particles are homogeneous, with no dissimilar metal contact interface, resulting in the lowest current collector cost.
[0087] Example 8
[0088] Self-supporting plate negative electrode without current collector: The same proportions and mixing process as in Example 2 (80wt% carbonyl iron powder, 15wt% bismuth powder, and 5wt% ferrous sulfide powder) were used, but without the current collector: the mixed powder was directly filled into the cavity of a 5cm×5cm graphite mold and leveled. A nickel strip guide was pre-embedded on one edge of the powder layer (embedded to a depth of about 8mm). The amount of powder filled corresponds to a molding thickness of about 1.5mm. The hot pressing and cooling processes were the same as in Example 2.
[0089] The resulting self-supporting plate-type negative electrode structure is complete and without any defects at the edges and corners; the measured porosity is 30.8%, and the three-point bending strength is about 8.1 MPa, which meets the mechanical integrity requirements under assembly operation and electrolyte immersion conditions; the interface between the nickel strip current guide and the active layer is covered and locked by solidified bismuth, and the interface contact resistance is negligible.
[0090] Electrochemical performance: 1C specific capacity 0.263 Ah / g, capacity retention 90.2% after 300 cycles, comparable to Example 2 (due to the absence of a metal mesh current collector and a slight increase in in-plane electrode resistance, the rate performance is slightly lower than Example 2). This demonstrates that the negative electrode can be self-supportingly formed without a current collector, relying on the mechanical strength of the continuous bismuth metal network. Eliminating the current collector further improves the electrode's mass energy density and reduces material costs, making it suitable for thick plate electrodes and cost-sensitive long-term energy storage scenarios.
[0091] Example 9
[0092] The bismuth powder in Example 2 was replaced with an equal mass of tin powder (D50 approximately 10 μm, purity not less than 99.9 wt%, melting point 231.9 °C), and the hot pressing temperature was adjusted accordingly to 260 °C (approximately 28 °C higher than the melting point of tin). The remaining processes were the same as in Example 2.
[0093] Molten tin wets iron particles in a hydrogen-containing atmosphere and forms a thin layer of FeSn2 intermetallic compound at the interface, forming a metallurgically bonded continuous conductive network; the measured peel strength is 13.5 N / cm, the sheet resistance is 9.1 mΩ / □, and the 1C specific capacitance is 0.257 Ah / g.
[0094] In Example 2, the bismuth powder was replaced with an equal mass of lead powder (D50 approximately 15 μm, purity not less than 99.9 wt%, melting point 327.5 °C), the hot pressing temperature was adjusted to 345 °C, and the rest of the process remained unchanged. Lead shrinks in volume during solidification and has no self-tightening effect. The measured peel strength is 11.9 N / cm. However, thanks to the high hydrogen evolution overpotential of lead, the hydrogen evolution side reaction at the charging end is effectively suppressed, and the 1C specific capacity is 0.252 Ah / g. This scheme must meet the environmental protection regulations of the local area when it is used.
[0095] The above results show that both tin and lead can form a continuous bonded conductive network and obtain usable electrochemical performance using the melt-bonding process of the present invention: the bismuth scheme has the best overall performance, the tin scheme has lower hot-pressing temperature and raw material cost, and the lead scheme has outstanding hydrogen evolution suppression.
[0096] Comparative Example 1 Traditional polyethylene adhesive electrodes: The control electrode was prepared according to the typical formulation of US10,374,261B2 and related literature: 66wt% carbonyl iron powder, 5wt% bismuth powder, 10wt% ferrous sulfide powder, 5wt% conductive carbon black, and 12wt% ultra-high molecular weight polyethylene binder. It was hot-pressed at 140℃ and 10MPa (below the melting point of bismuth, bismuth is only an additive, and polyethylene is responsible for bonding).
[0097] Actual measurements showed: active component content approximately 73%, peel strength 11.2 N / cm, electrode internal resistance approximately 23.5 mΩ, 1C specific capacity 0.283 Ah / g, and 500-cycle retention rate 90.8%. Compared to Example 2, this invention is superior in internal resistance (-27%), peel strength (+37%), and active component content (+12 percentage points), while the 1C specific capacity is comparable (difference approximately 2%, within the error range). A comprehensive comparison can be found in [link to comparison]. Figure 10 .
[0098] In this comparative example, the bismuth content is 5 wt%, but because the hot pressing temperature is lower than the melting point of bismuth and the bismuth does not melt, it is necessary to rely on 12 wt% polyethylene to form it. In contrast, in Example 6, 5 wt% fine bismuth powder can be formed independently by super-melting point hot pressing. The two completely different forms and functions under the same bismuth content demonstrate the substantiality of the melt bonding of this invention.
[0099] Comparative Example 2 Contains only bismuth, no anti-passivation additives, and no sulfur-replenishing electrolyte: The ratio was 80wt% carbonyl iron powder and 20wt% bismuth powder. The process was the same as in Example 2. The test electrolyte was a 30wt% potassium hydroxide aqueous solution without sulfur supplementation additives.
[0100] The measured C / 2 charging efficiency remained at a normal level (bismuth's hydrogen evolution suppression function functioned normally), but the 3C specific capacity was only 0.038 Ah / g, the charge transfer resistance at the end of discharge was as high as 198Ω, and the retention rate after 500 cycles was only 85.3%. Figure 7 , Figure 9 As shown in the figure, this comparative example demonstrates that bismuth primarily addresses structural bonding, conductivity, and hydrogen evolution at the charging end, while the suppression of high-rate passivation at the discharge end is undertaken by sulfur species, with the two functions being orthogonal. Furthermore, the electrode in this comparative example exhibits intact forming, a continuous conductive network, and normal charging efficiency. This indicates that the two-component active layer without anti-passivation additives can be normally melt-bonded and formed while maintaining high charging efficiency. It is suitable for low-rate, long-duration energy storage scenarios, or high-rate discharge performance can be restored by using electrolyte sulfur replenishment (adding 0.5–5 mmol / L potassium sulfide or sodium sulfide to the electrolyte).
[0101] Comparative Example 3 Hot pressing in a pure nitrogen atmosphere without hydrogen: The process is the same as in Example 2, but the hot pressing atmosphere is pure nitrogen (without hydrogen).
[0102] Scanning electron microscopy of the electrode cross-section revealed numerous unwetting voids at the bismuth-iron interface, with a peel strength of only 7.5 N / cm. Localized detachment of the active layer occurred after 30 cycles. This indicates that for iron powder with a significant oxide film on its surface, a hydrogen-containing reducing atmosphere can effectively remove the oxide film and restore the wettability of liquid bismuth, significantly impacting the quality of the melt bond. Therefore, hot pressing is preferably performed in a hydrogen-containing reducing atmosphere.
[0103] Comparative Example 4 In Example 2, the metallic bismuth powder was replaced with Bi2O3 powder in equimolar amounts of bismuth (the remaining components and processes remained unchanged, the hot pressing temperature was reduced to 140°C and 12wt% polyethylene adhesive was added to maintain the molding, since Bi2O3 has a high melting point of 817°C and cannot be melted and bonded).
[0104] Actual charging efficiency test of the first 10 cycles: The first cycle was significantly lower, and it stabilized around the 8th to 10th cycles. Figure 8 As shown; however, Example 2 approached a stable level in the first cycle. Based on the cumulative charge in the first 10 cycles, Comparative Example 4 showed a significant cumulative efficiency loss during the activation period. This comparison demonstrates the "zero activation period" effect of directly adding bismuth powder according to the present invention, and shows that the Bi2O3 precursor cannot achieve molten bonding at the hot-pressing temperature of the present invention.
[0105] The performance testing methods for Examples 1-9 and Comparative Examples 1-4 are as follows: Charging efficiency: Charged to 125% of rated capacity at C / 2 rate, the evolved gas was collected by water displacement and confirmed as hydrogen by gas chromatography (thermal conductivity detector, 5A molecular sieve column). Efficiency was calculated as: discharge amount ÷ (charge amount - hydrogen equivalent charge) × 100%. Porosity: Nitrogen adsorption method combined with mercury porosimetry. Peel strength: Tested according to GB / T2792-2014, with a 90° peel angle and a rate of 50 mm / min. Flexural strength: Three-point bending method (span 20 mm, loading rate 0.5 mm / min). Sheet resistance: Four-probe method. Cyclic test: C / 2 rate, 100% depth of discharge, 500 cycles.
[0106] Application Example 1 Long-term energy storage single cell: The negative electrode from Example 2 (a 10cm × 10cm enlarged model, with a surface density deviation of ±4.2%, verifying the feasibility of process scale-up) was assembled with a bifunctional air positive electrode (Fe-NC catalyst layer / PTFE waterproof and breathable layer / stainless steel support mesh) and a polypropylene separator to form a single-cell iron-air battery. The electrolyte was 30wt% potassium hydroxide (containing 2mmol / L potassium sulfide sulfur supplementation additive, corresponding to the electrolyte sulfur supplementation scheme of this invention). C / 10 rate continuous charge-discharge: discharge plateau voltage approximately 1.05V, charging plateau voltage approximately 1.9V, capacity retention rate 96.5% after 100 cycles. Designed for a discharge duration of over 10 hours, it is suitable for grid peak shaving and valley filling and renewable energy consumption.
[0107] Application Example 2 Photovoltaic supporting energy storage modules: Twenty individual units as described in Application Case 1 were connected in series to form an approximately 24V energy storage module, which, together with a 1kW photovoltaic module and a charge / discharge management circuit, constituted an off-grid microgrid demonstration system. During the day, the photovoltaic system charged at approximately C / 20, and at night it discharged at approximately C / 30 to supply lighting and monitoring loads. After 30 days of continuous operation (approximately 30 shallow charge / discharge cycles), there was no measurable capacity degradation in the module, verifying the adaptability of the negative electrode of this invention under real intermittent renewable energy operating conditions.
[0108] Application Example 3 Backup power system: Utilizing the zero activation period characteristic (the initial charging efficiency is close to a stable level) and low self-discharge of the negative electrode of this invention, the module is configured as a backup power supply for communication base stations: it is kept fully charged during normal float charging and immediately discharged when the mains power is interrupted. Tests show that the self-discharge capacity loss after 48 hours of full charge is less than 8%, and the initial capacity utilization rate after power failure switching is not less than 97% of the rated value, which is significantly better than the Bi2O3 precursor scheme that requires multiple activation cycles (the initial capacity utilization rate of Comparative Example 4 under the same conditions is about 88%).
[0109] The above embodiments and application examples demonstrate that the present invention achieves a polymer-free and carbon-based conductive agent-free iron-air battery negative electrode through a low-melting-point metal (preferably bismuth) fusion bonding strategy. The technical effects of solidification self-tightening bonding, triple-functional integration, and hydrogen-atmosphere super-melting-point hot pressing with zero activation have all been experimentally verified. Examples 4-9 further verify the feasibility of extended solutions such as the hot pressing process window and 500MPa pressure upper limit, bismuth-tin alloy, 5wt% bismuth lower limit, zinc sulfide additive, nickel mesh / stainless steel mesh / iron mesh current collector, self-supporting molding without current collector, and low-melting-point metals like tin and lead. Equivalent substitutions or obvious modifications made by those skilled in the art based on the technical solutions of this invention should all fall within the protection scope of the claims of this invention.
[0110] Therefore, it can be seen that the low-melting-point metal fusion bonded iron-air battery anode, its preparation method and application provided by the present invention, wherein the active layer is composed of only two or three types of components: iron-based active particles, low-melting-point metal bonded conductive phase and optional anti-passivation additives, completely eliminating polymer binders and carbon-based conductive agents, and increasing the proportion of active components from about 73% to about 85%; The conductivity is significantly improved, and the electrode ohmic internal resistance is reduced from about 23.5 mΩ to about 17.1 mΩ, a reduction of about 27%. The mechanical bonding is significantly enhanced, with the 90° peel strength increasing from approximately 11.2 N / cm to approximately 15.4 N / cm, an increase of approximately 37%. With zero activation period, the first-cycle charging efficiency is close to a stable level when using elemental metal powder, eliminating the activation loss of the precursor solution. The electrochemical performance has reached the current advanced level, with a 1C specific capacity of 0.278 Ah / g, a 3C specific capacity of 0.183 Ah / g, and a capacity retention rate of 91.3% after 500 full-depth cycles. The process is mild, safe, and scalable. The hot pressing temperature for the pure bismuth solution is only 280–320°C, while the bismuth-tin alloy solution can be further reduced to 150–220°C. It is compatible with roll-to-roll continuous hot pressing equipment. Green and environmentally friendly, bismuth is non-toxic and does not contain harmful heavy metals such as mercury, which meets environmental compliance requirements. When using lead or lead-containing alloy solutions, the environmental regulations of the local area must be met. The raw materials are flexible and can reduce costs. The iron-based active particles can be made from inexpensive reduced iron powder alone or mixed with carbonyl iron powder. The structure is flexible and optional, with both anti-passivation additives and current collectors being optional components. Solid additives are selected for high-rate scenarios, while additives can be omitted for low-rate scenarios or electrolyte sulfur replenishment scenarios. Thin electrodes can be formed by combining current collectors, while thick plate electrodes can be formed by self-supporting, adapting to diverse application needs.
[0111] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A low-melting-point metal fusion-bonded iron-air battery negative electrode, characterized in that, The negative electrode includes an active layer comprising iron-based active particles and a low-melting-point metal-bonded conductive phase. The active layer contains no polymer binder or carbon-based conductive agent. The low-melting-point metal-bonded conductive phase is a continuous three-dimensional metal network formed by a melting-solidification process of a low-melting-point metal with a melting point of 130–350°C. This continuous three-dimensional metal network forms a bridging structure at the contact necks of adjacent iron-based active particles, bonding the iron-based active particles together and forming a continuous electron conduction pathway within the active layer. The content of the low-melting-point metal-bonded conductive phase, based on the total mass of the active layer, is 5–25 wt%.
2. The low-melting-point metal fusion bonded iron-air battery negative electrode according to claim 1, characterized in that, The low-melting-point metal is bismuth, tin, or lead, or an alloy containing at least one of bismuth, tin, or lead.
3. The low-melting-point metal fusion bonded iron-air battery negative electrode according to claim 2, characterized in that, The low-melting-point metal is bismuth or a bismuth alloy that expands in volume upon solidification. After melting, it solidifies, and the volume expansion of the solidified solid is constrained by the skeleton formed by the iron-based active particles, which is converted into internal pressure, forming a press-fit mechanical lock on the iron-based active particles. The bismuth is pure bismuth with a purity of not less than 99 wt%, and the bismuth alloy is a bismuth-tin alloy with a tin content of not more than 42 wt% and a melting point of 138–271.4 °C. The low-melting-point metal-bonded conductive phase is an independent pure metal phase, and there are no intermetallic compounds between it and the iron-based active particles.
4. The low-melting-point metal fusion bonded iron-air battery negative electrode according to claim 1, characterized in that, The content of the low-melting-point metal-bonded conductive phase is 5-25 wt% based on the total mass of the active layer; the porosity of the active layer is 20%-38%.
5. The low-melting-point metal fusion bonded iron-air battery negative electrode according to claim 1, characterized in that, The iron-based active particles are one of carbonyl iron powder, reduced iron powder, or a mixture thereof; the iron content of the carbonyl iron powder is not less than 99.5 wt%.
6. The low-melting-point metal fusion bonded iron-air battery negative electrode according to claim 1, characterized in that, The active layer further includes anti-passivation additive particles, which are one or more of ferrous sulfide, ferrous disulfide, zinc sulfide, sodium sulfide, and potassium sulfide; the content of the anti-passivation additive particles is 3 to 15 wt% based on the total mass of the active layer.
7. The low-melting-point metal fusion bonded iron-air battery negative electrode according to claim 1, characterized in that, The negative electrode also includes a current collector, the active layer is laminated to at least one surface of the current collector, and the continuous three-dimensional metal network anchors the active layer to the surface of the current collector. The current collector is a nickel-plated copper mesh, nickel mesh, nickel sheet, nickel foam, stainless steel mesh, or iron mesh. Alternatively, the negative electrode is a self-supporting electrode without current collectors, which maintains the mechanical integrity of the active layer by relying on the continuous three-dimensional metal network, and draws out the current through metal current drawers embedded or welded to the active layer.
8. A method for preparing a low-melting-point metal fusion-bonded iron-air battery negative electrode as described in any one of claims 1 to 7, characterized in that, Includes the following steps: Step 1: Dry mix the raw material powder, including iron-based active powder and low-melting-point metal powder, to obtain a mixed powder. Step 2: The mixed powder is spread on at least one surface of the current collector, or the mixed powder is filled into the cavity of the hot press mold; Step 3: Heat to a temperature 10-50°C higher than the melting point of the low-melting-point metal, apply a pressure of 10-500 MPa and hold for 3-15 minutes, so that the molten low-melting-point metal wets the particle surface of the iron-based active powder and fills the gaps between the particles. Step four: Under the condition of maintaining auxiliary pressure, the temperature is reduced to below the melting point of the low melting point metal at a rate of 1-5℃ / min, so that the low melting point metal solidifies, cools and demolds to obtain the negative electrode of the iron-air battery.
9. An iron-air battery, characterized in that: The battery comprises a low-melting-point metal molten bonded iron-air battery negative electrode as described in any one of claims 1 to 7, a bifunctional air positive electrode, a separator, and an alkaline electrolyte; wherein the alkaline electrolyte is an aqueous solution of potassium hydroxide with a mass concentration of 10% to 35%.
10. An application of the iron-air battery as described in claim 9 in grid energy storage, renewable energy power generation supporting energy storage, or backup power systems.
Citation Information
Patent Citations
Negative electrodes for electrochemical cells
CN112805851A
High efficiency iron electrode and additives for use in rechargeable iron-based batteries
EP2721688B1
High efficiency iron electrode and additives for use in rechargeable iron-based batteries
US10374261B2
Traction-engine
US363415A
Method for making zinc electrodes for alkaline-zinc batteries
US5124120A
